2016
DOI: 10.1371/journal.pone.0153277
|View full text |Cite
|
Sign up to set email alerts
|

Neandertal versus Modern Human Dietary Responses to Climatic Fluctuations

Abstract: The Neandertal lineage developed successfully throughout western Eurasia and effectively survived the harsh and severely changing environments of the alternating glacial/interglacial cycles from the middle of the Pleistocene until Marine Isotope Stage 3. Yet, towards the end of this stage, at the time of deteriorating climatic conditions that eventually led to the Last Glacial Maximum, and soon after modern humans entered western Eurasia, the Neandertals disappeared. Western Eurasia was by then exclusively occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 56 publications
0
26
0
4
Order By: Relevance
“…However, late Neanderthals may have had a less diverse diet than modern humans ( 60 ). In open grasslands, Neanderthals’ exclusive diet was meat from terrestrial animals, whereas modern human Aurignacian also exploited plant and aquatic foods ( 60 , 61 ). The frequently observed cultural hiatuses, however, do not suggest a direct competitive displacement of Neanderthals, but rather a higher vulnerability to rapid environmental change and ecologic stress in the open landscape during cold and arid GS12–GS10.…”
Section: The Relationship Between Demography and Climate Change Durinmentioning
confidence: 99%
“…However, late Neanderthals may have had a less diverse diet than modern humans ( 60 ). In open grasslands, Neanderthals’ exclusive diet was meat from terrestrial animals, whereas modern human Aurignacian also exploited plant and aquatic foods ( 60 , 61 ). The frequently observed cultural hiatuses, however, do not suggest a direct competitive displacement of Neanderthals, but rather a higher vulnerability to rapid environmental change and ecologic stress in the open landscape during cold and arid GS12–GS10.…”
Section: The Relationship Between Demography and Climate Change Durinmentioning
confidence: 99%
“…In northern latitudes, they were predominantly carnivorous, had advanced leather processing technology (using lissoirs, probably later borrowed by AMH [45]), with modeling studies suggesting advanced winter clothing [46] using stone and bone awls (such as found in the Grotte du Renne) as sewing aids [47], but in general their diet was apparently very flexible and adapted to the local environment, including both meat and vegetable foods [48] to varying proportions [13,[49][50][51]. Bitter medicinal herbs were consumed [52], a Neanderthal with dental abscess appears to have treated himself with poplar bark (a source of salicylic acid) and possibly mold-produced antibiotics , new analyses suggesting that there were no differences in raw material efficiency [55], that bone was used for tools [56], that hafting might go back to 240-270 kya [57] and that manganese dioxide was used to produce fire on demand 50 kya [58], and only after c. 40 kya (as the Neanderthals were disappearing) did AMH technology become clearly superior.…”
Section: Neanderthal Cognition As Evidenced By Archeologymentioning
confidence: 99%
“…Since 2005, researchers have demonstrated its efficacy via comparative and experimental studies using extinct and extant organisms (e.g., Calandra, Schulz, Pinnow, Krohn, & Kaiser, ; Delezene, Teaford, & Ungar, ; DeSantis, Schubert, Scott, & Ungar, ; Estalrrich & Rosas, ; Purnell & Darras, ; Ragni, Teaford, & Ungar, ; Schulz, Calandra, & Kaiser, ; Scott et al, ; Scott et al, ; Scott, Teaford, & Ungar, ; Shearer et al, ; Teaford & Ungar, ; Teaford, Ungar, Taylor, Ross, & Vinyard, ; Ungar, Grine, & Teaford, ). Specifically, the DMTA derived from living primates has been especially integral in the contextualization of fossil primate and hominin diets (e.g., Delezene, Zolnierz, Teaford, Grine, & Ungar, ; El Zaatari, Grine, Ungar, & Hublin, ; Grine, Ungar, Teaford, & El Zaatari, ; Karriger, Schmidt, & Smith, ; Scott et al, ; Ungar, ; Ungar et al, ; Ungar, Krueger, Blumenschine, Njao, & Scott, ; Ungar & Scott, ; Ungar, Scott, & Steininger, ; Ungar & Sponheimer, ) and recent experimental work has allowed us to better understand the mechanics of microwear formation (e.g., Daegling, Hua, & Ungar, ; Hua, Brandt, Meullenet, Zhou, & Ungar, ; Xia et al, , ).…”
mentioning
confidence: 99%